FINANCIAL DISTRESS ANALYSIS USING ALTMAN AND ZMIJEWSKI ON TOURISM INDUSTRY - Ginta, Rivald Fathur Ghaffary Lenggo; Handri (Kajian Akuntansi, 2024)
This study examines financial distress scenarios in the tourism and recreation industry using the Altman Z-score and Zmijewski X-Score methodologies. Employing a quantitative descriptive research approach with purposive sampling, the study analyzes 12 publicly listed companies on the Indonesia Stock Exchange from 2019 to 2022. The results indicate that PT. Eastparc Hotel is the most financially stable, contrasting with PT. Bukit Uluwatu Villa as the weakest. While both methods yield different results, the disparity is not highly significant due to the varied components analyzed in the financial reports. The research recommends using multiple analytical methods for bankruptcy prediction to allow for accuracy assessment and to determine the suitability of each model for specific companies. Keywords     : Financial distress, Tourism and recreation industry, Z-score altman, zmijewski x-score.